Method for detecting concentration of malachite green based on luminescent biomass edgeworthia chrysantha carbon dot fluorescent probe
By using fluorescent probes constructed with luminescent biomass aromatic carbon dots and bovine serum albumin functionalized gold nanoclusters, the existing malachite green detection methods are solved, and fast, accurate and low-cost detection is achieved, with high sensitivity and green environmental protection.
Patent Information
- Application Number
- CN202510028135.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-18
AI Technical Summary
The existing malachite green detection methods are cumbersome and costly, making it difficult to meet the fast, efficient and low-cost testing requirements in food supervision.
A fluorescent probe constructed based on water-soluble luminescent biomass aromatic carbon dots was used to determine the malachite green concentration by mixing the luminescent biomass aromatic carbon dot solution and bovine serum albumin functionalized gold nanocluster solution, and combining the dual emission fluorescence intensity ratio or B/(G+R) value.
It realizes fast, accurate and low-cost malachite green detection, with high sensitivity, good selectivity, green and environmentally friendly, simple and easy to operate, and is suitable for fast on-site visual monitoring of food and environmental safety.
Smart Images

Figure CN119845914A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of food detection, and specifically is a method for detecting the concentration of malachite green based on a luminescent biomass aroma carbon dot fluorescent probe. Background Art
[0002] Malachite green is a toxic triphenylmethane organic chemical commonly used in industrial dyes. It can also kill fungi, bacteria and parasites, and has potential carcinogenic, teratogenic and mutagenic effects. It is easy to exist in aquatic products and the environment for a long time, and it is prohibited to add it to food or pollution-free aquaculture. However, it is effective against saprolegniasis of fish and fish eggs. There is currently no specific drug on the market that can solve saprolegniasis in a short time. Due to the lack of cheap and effective alternatives, it is still illegally used by criminals in aquaculture, and it accumulates in the human body through the food chain and is difficult to metabolize. In recent years, some criminals have illegally used malachite green for tea dyeing in order to improve the appearance of inferior tea. The illegal addition of malachite green is harmful to public health and has adverse effects on the development of food and environmental safety industries. There is an urgent need for a highly sensitive malachite green detection method.
[0003] The quantitative determination of malachite green is beneficial to food and environmental safety monitoring. The methods reported for malachite green detection include high performance liquid chromatography, surface enhanced Raman scattering, and enzyme-linked immunosorbent assay. The above methods require complex pretreatment processes and high requirements for operators, and it is difficult to meet the requirements of rapid, efficient, and low-cost detection in actual food supervision. New methods developed in recent years, such as colorimetry, nanomaterial molecular imprinting, fluorescent probe, and electrochemical analysis, have the advantages of low detection limits and high sensitivity compared with traditional methods, but the operation is cumbersome, the detection time is long, and derivatives or expensive instruments are required, and sometimes there are false positive or false negative problems. Therefore, it is of great research significance to find new fast, accurate, low-cost, simple, and highly sensitive spectral detection methods. Summary of the invention
[0004] In view of the problems of complicated operation and high cost in the new method for detecting malachite green in the prior art, the present invention provides a method for detecting the concentration of malachite green based on a fluorescent probe of luminescent biomass incense carbon dots. The method of the present invention is based on a fluorescent probe constructed from water-soluble luminescent biomass incense carbon dots, and the concentration of malachite green is determined according to the fluorescent signal emitted by the luminescent biomass incense carbon dots. It is a new use of water-soluble luminescent carbon dot fluorescent materials and meets the actual use requirements.
[0005] The fluorescent probe comprises a luminescent biomass osmanthus carbon dot solution prepared from osmanthus leaves, and the fluorescent probe also comprises a bovine serum albumin functionalized gold nanocluster solution. When in use, the luminescent biomass osmanthus carbon dot solution and the bovine serum albumin functionalized gold nanocluster solution are mixed.
[0006] The present invention provides three methods for detecting the concentration of malachite green based on fluorescent probes of luminescent biomass aromatic carbon dots.
[0007] The first method is to mix the malachite green standard and the sample to be tested with the fluorescent probe, calculate the dual emission fluorescence intensity ratio to draw a standard curve, and detect the malachite green concentration of the sample to be tested, specifically in the following steps:
[0008] Step 1, respectively mix the malachite green standard and the sample to be tested with the fluorescent probe, and set up a blank system without the malachite green standard or the sample to be tested, test the mixed solution and the blank system under the same conditions, respectively measure their dual emission fluorescence intensities, and calculate the dual emission fluorescence intensity ratio of the mixed solution and the blank system.
[0009] The dual emission fluorescence intensity test conditions are: the fluorescence intensity is measured under the conditions of an excitation wavelength of 350 nm, detection wavelengths of 452 nm and 627 nm, an incident slit of 5 nm, and an exit slit of 5 nm.
[0010] Step 2, drawing a standard curve according to the dual emission fluorescence intensity ratio of the malachite green standard obtained in step 1;
[0011] The dual emission fluorescence intensity ratio is: the ratio of the fluorescence intensity at a wavelength of 452nm to the fluorescence intensity at a wavelength of 627nm;
[0012] When drawing the standard curve, the ratio of the dual emission fluorescence intensity of the fluorescent probe after adding the malachite green standard is used as the ordinate, and the concentration of the malachite green standard is used as the abscissa.
[0013] Step 3: Substitute the dual-emission fluorescence intensity ratio of the sample to be tested into the standard curve to obtain the content of malachite green in the sample to be tested.
[0014] The standard curve drawn by the first method has a linear equation of: y = 0.2173x + 2.9036, R 2 The detection limit of malachite green is 24.5nM, and it shows good linearity when the concentration of malachite green is between 0 and 40μM.
[0015] The second method is to mix the malachite green standard and the sample to be tested with the fluorescent probe, calculate the B / (G+R) value to draw a standard curve, and detect the malachite green concentration of the sample to be tested, specifically in the following steps:
[0016] Step 1, mixing the malachite green standard and the sample to be tested with the fluorescent probe respectively;
[0017] Step 2, converting the color signal of the mixed solution of the malachite green standard and the fluorescent probe into a digital signal RGB, recording the R, G, and B channel signals, calculating the B / (G+R) value and drawing a standard curve;
[0018] A standard curve is drawn with the color digital signal B / (G+R) value of the probe after adding the malachite green standard as the ordinate and the concentration of the malachite green standard as the abscissa.
[0019] Step 3: Substitute the B / (G+R) value of the sample to be tested into the standard curve to obtain the content of malachite green in the sample to be tested.
[0020] The second method of drawing the standard curve regression equation is: y = 0.0081x + 0.5265 (R 2 =0.9975), the corresponding detection limit was 34.8 nM, and B / (G+R) showed a good linear relationship with the concentration of malachite green in the range of 0 to 50 μM.
[0021] The third method is to drop the malachite green standard and the sample to be tested onto the test paper soaked with the fluorescent probe, draw a standard curve with the calculated B / R value, and detect the malachite green concentration of the sample to be tested, specifically in the following steps:
[0022] Step 1, respectively drop the malachite green standard solution and the sample to be tested onto the test paper soaked with the luminescent biomass fragrance carbon dot fluorescent probe, record the color change of the test paper, convert it into a digital signal RGB, and record the R and B channel signals;
[0023] Step 2, drawing a standard curve according to the B / R value of the malachite green standard solution;
[0024] A standard curve is drawn with the color digital signal B / R value of the probe test paper after adding the malachite green standard as the ordinate and the concentration of the malachite green standard as the abscissa;
[0025] Step 3: Substitute the B / R value of the sample to be tested into the standard curve to obtain the content of malachite green in the sample to be tested.
[0026] In the above three application methods, the solvent of the malachite green standard solution is a BR buffer solution; preferably, the solvent of the malachite green standard solution is a BR buffer solution of pH 7.
[0027] In the above three application methods, the conditions for mixing the malachite green standard and the sample to be tested with the fluorescent probe are:
[0028] The experimental temperature is room temperature 10-32°C; the pH of the mixed solution is 4-10; and the reaction time is 1-5 minutes. Preferably, the reaction temperature is specifically 25°C, the reaction pH is specifically 7, and the reaction time is specifically 1 minute.
[0029] In the present invention, the preparation steps of the luminescent biomass osmanthus carbon dot solution are as follows: clean the osmanthus leaves, dry them, and make them into powder; fully mix the osmanthus leaf powder and BR buffer solution, put them in a high-pressure reactor, heat them for a period of time, naturally cool them to room temperature, filter them through a filter membrane, collect the clarified liquid, and dialyze them with deionized water to obtain the luminescent biomass osmanthus carbon dot solution; the mass volume ratio of the osmanthus leaf powder to the BR buffer solution is (0.10-0.30) g: 10 mL, and the pH value of the BR buffer solution varies in the range of 2-10; the heating conditions are: 120-200° C., 8-16 hours.
[0030] In the present invention, in the preparation step of the luminescent biomass aromatic carbon dot solution, the mass volume ratio of aromatic cinnamon leaf powder to BR buffer solution is 0.19g:10mL, and the pH value of the BR buffer solution is 5; the heating conditions are: 180°C, 12 hours; the maximum fluorescence excitation peak of the prepared biomass aromatic carbon dots is at 325nm, and the maximum emission peak is at 455nm; there are two characteristic absorption peaks at 280nm and 325nm; the average particle size is 3.9±0.5nm.
[0031] In the present invention, the preparation steps of the bovine serum albumin functionalized gold nanocluster solution are as follows: 4 mL of 1% tetrachloroauric acid aqueous solution is added to 10 mL of 50 mg / mL bovine serum albumin solution while magnetically stirring, and the mixture is evenly mixed, and vigorously stirred for 3 minutes, and 1 mL of 1M NaOH solution is added to the mixed solution, and after stirring and reacting for 14 hours in a dark environment, the solution is diluted to 50 mL, and finally a bovine serum albumin functionalized gold nanocluster solution is obtained, and the concentration is 2 mM. The prepared bovine serum albumin functionalized gold nanocluster has an average particle size of 2.2±0.4 nm; its maximum fluorescence excitation peak is 490 nm, and the maximum emission peak is 636 nm.
[0032] In the present invention, in the fluorescent probe, the volume ratio of the biomass aroma carbon dot solution and the bovine serum albumin functionalized gold nanocluster solution is 15:90.
[0033] Compared with the prior art, the implementation effects of the present invention are as follows:
[0034] 1) The present invention provides a novel fluorescent probe based on luminescent biomass incense-forming carbon dots for detecting malachite green. The experimental reaction system of the fluorescent probe consists of biomass incense-forming carbon dots and gold nanoclusters functionalized with bovine serum albumin. The biomass incense-forming carbon dots prepared according to the present invention have a strong fluorescence signal. When gold nanoclusters are added, the fluorescence signal of the biomass incense-forming carbon dots is weakened. As the volume of the added gold nanoclusters increases, the fluorescence signal gradually increases. After the addition of malachite green, the dual-emission fluorescence signal of the reaction system is significantly quenched, thereby generating a detectable signal.
[0035] 2) This method is based on fluorescent probes and provides a new way to detect malachite green. It can also use smartphones to assist in portable on-site rapid detection, which has potential significance for food safety and environmental pollutant detection.
[0036] 3) The detection method of the present invention has the characteristics of good selectivity, high sensitivity, green environmental protection, simplicity and ease of use, etc. The detection method of the present invention has the characteristics of self-calibration and precise quantitative measurement.
[0037] 4) The detection method of the present invention can be extended to the determination of malachite green content in foods such as aquatic products.
[0038] 5) The establishment of the method of the present invention can provide new ideas for rapid on-site visual monitoring of food and environmental safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The ultraviolet absorption spectrum, fluorescence excitation spectrum and emission spectrum of the biomass aroma carbon dots prepared in Example 1;
[0040] Figure 2 The fluorescence properties of the luminescent biomass aroma carbon dots prepared in Example 1;
[0041] Figure 3 The fluorescence spectra of the luminescent biomass agarwood carbon dot fluorescent probe solution (agarwood carbon dot biosensor) after adding different concentrations of malachite green in Example 2;
[0042] Figure 4 This is the relationship between the concentration and fluorescence intensity ratio of malachite green detected by using the luminescent biomass agarwood carbon dot fluorescent probe solution (agarwood carbon dot biosensor) in Example 2 (standard curve). DETAILED DESCRIPTION
[0043] The technical solution of the present invention is described in detail below through embodiments, but the protection scope of the present invention is not limited to the embodiments.
[0044] The content of the present invention will be described below with reference to specific embodiments.
[0045] Example 1: Preparation of biomass aromatic carbon dot fluorescent probe
[0046] Step 1: Preparation of biomass aromatic carbon dot solution
[0047] The specific steps for the synthesis of biomass aroma carbon dots are as follows:
[0048] The leaves of the osmanthus tree were cleaned, dried for 12 hours, and made into powder. Different masses of osmanthus leaf powder were fully mixed with 10 mL of BR buffer solution with different pH values, placed in a high-pressure reactor, heated at different temperatures for different times, naturally cooled to room temperature, filtered through a 0.22 μM filter membrane, and the clarified liquid was collected. The clear liquid was dialyzed with deionized water for 24-48 hours to remove impurities, and finally the luminescent biomass osmanthus carbon dot solution was obtained as a light brown solution, which was stored at 4°C away from light for future use.
[0049] Preparation method of BR buffer with different pH values: Prepare 0.1L of 0.04mol / L mixed acid solution, which is composed of 4.60mL acetic acid, 5.48mL phosphoric acid and 4.9464g boric acid. Add different amounts of 0.2mol / L sodium hydroxide solution, adjust the ratio of the two solutions, and prepare BR buffer solutions with different pH values.
[0050] The pH value of the BR buffer solution was adjusted (the pH value range was 2-10) to explore its effect on the synthesis process. Next, a gradient control experiment of the reaction temperature was conducted to determine the optimal reaction temperature, which ranged from 120-200°C; then, the effect of the reaction time on the synthesis of the aromatic carbon dots was studied to ensure the efficiency of the synthesis process and the quality of the product, with a reaction time of 8-16 hours. Finally, the effect of the sample input amount was investigated, and an experiment was conducted to optimize the sample addition amount, with the amount of aromatic powder added being 0.10-0.30g.
[0051] In this embodiment, the medicinal value of the leaves of the osmanthus tree is used as a green and environmentally friendly carbon source. The reaction temperature, reaction time, pH value of the buffer solution, and the mass / volume ratio of the carbon source powder to the buffer solution are combined to study the influence of four key factors on the fluorescence intensity of the synthesized osmanthus tree carbon dots, and obtain the carbon dots with the best fluorescence effect. The optimal synthesis conditions of the biomass osmanthus tree carbon dots are finally determined as follows: the osmanthus tree leaves are cleaned, dried for 12 hours, and made into powder; 0.19g of the osmanthus tree leaf powder is fully mixed with 10mL of pH5 BR buffer, placed in an autoclave, heated for reaction at 180°C for 12 hours, cooled naturally to room temperature, filtered through a 0.22μM filter membrane, and the clarified liquid is collected and dialyzed with deionized water for 24-48 hours to remove impurities. The luminescent biomass osmanthus tree carbon dot solution is finally obtained as a light brown solution, which is stored at 4°C in the dark for standby use.
[0052] Step 2: Characterization of biomass aroma carbon dots
[0053] The biomass aroma carbon dot solution synthesized under the optimal synthesis conditions was subjected to the characterization test of step two.
[0054] The excitation spectrum and emission spectrum of the biomass aroma carbon dot solution prepared in step 1 were measured using a fluorescence spectrometer (PerkinElmer LS-55). Figure 1 As shown in the figure, the maximum excitation peak of the biomass aroma carbon dots prepared in step 1 is at 325nm, the maximum emission peak is at 455nm, and the fluorescence emission is strong, which indicates that the luminescent biomass aroma carbon dots prepared in step 1 are luminescent biomass aroma carbon dots. Under different excitation wavelengths, the emission spectrum has a maximum emission peak at 455nm as the excitation wavelength increases from 310nm to 390nm, indicating that the prepared biomass aroma carbon dots have fluorescence properties that are not dependent on the excitation wavelength. For details, see Figure 2 The strongest emission peak appears at an excitation wavelength of 325 nm.
[0055] The infrared absorption spectrum of the luminescent biomass aroma carbon point prepared in step 1 was measured by infrared spectrometer (NEXUS-670); the luminescent biomass aroma carbon point prepared in step 1 was 3200-3700cm -1 There is a broad absorption band at 1576cm, which is the stretching vibration of NH / OH. -1 The characteristic peak at 1751cm is due to CO. -1 The characteristic peak at 1300cm is caused by C=O. -1 The peaks on the left and right are attributed to CN, indicating that the luminescent biomass aromatic carbon dots have hydrophilic functional groups such as carboxyl, hydroxyl, and amine, and have good water solubility.
[0056] The ultraviolet-visible absorption spectrum of the luminescent biomass aroma carbon dots prepared in step 1 was measured using an ultraviolet-visible spectrophotometer (UV-2600); the luminescent biomass aroma carbon dots prepared in step 1 had two characteristic absorption peaks at 280nm and 325nm.
[0057] The morphology and particle size of the luminescent biomass aroma carbon dots prepared in step one were measured using a high-resolution transmission electron microscope (JEM-2100); the luminescent biomass aroma carbon dots prepared in step one were spherical and evenly distributed, with an average particle size of 3.9±0.5 nm.
[0058] Step 3. Preparation and characterization of gold nanocluster solution
[0059] 4 mL of 1% aqueous tetrachloroauric acid solution was added to 10 mL of 50 mg / mL bovine serum albumin solution at 37°C while magnetically stirring, and the mixture was evenly mixed. The mixture was stirred vigorously for 3 minutes, and 1 mL of 1 M NaOH solution was added to the mixed solution. The mixture was stirred at 37°C in the dark for 14 hours, and the color of the solution changed from light yellow to dark to obtain a light brown solution. The solution was diluted to 50 mL to finally obtain a bovine serum albumin functionalized gold nanocluster solution with a concentration of 2 mM, which was stored in the dark at 4°C for future use.
[0060] High-resolution transmission electron microscopy showed that the prepared bovine serum albumin functionalized gold nanoclusters were spherical, well dispersed, with an average particle size of 2.2±0.4nm. The maximum fluorescence excitation peak was 490nm, and the maximum emission peak was 636nm.
[0061] Step 4: Fluorescent probe based on biomass aroma carbon dots
[0062] When in use, add 15 μL of the luminescent biomass fragrance carbon dot solution prepared according to the optimal preparation conditions in step 1 to 90 μL of the gold nanocluster solution prepared in step 3. This volume condition has the best detection performance, which is the luminescent biomass fragrance carbon dot fluorescent probe solution.
[0063] Example 2: Application of luminescent biomass aromatic carbon dots in determining malachite green content
[0064] 1. Mixing the malachite green standard and the sample to be tested with the fluorescent probe, testing the dual emission fluorescence intensity ratio and drawing a standard curve.
[0065] 1. The luminescent biomass aroma-forming carbon dots prepared in Example 1 were dissolved in a BR buffer solution at pH 7 to obtain a solution I; in the solution I, the volume of the luminescent biomass aroma-forming carbon dots prepared in Example 1 was 15 μL.
[0066] 2. Add the gold nanoclusters prepared in Example 1 to the pre-prepared solution I, and add the volume of the gold nanocluster solution to 90 μL. Take a series of 100 μM malachite green standards with different volume concentrations, dissolve them in a pH 7 BR buffer solution, and prepare 0-40 μM malachite green solutions with different concentrations. Add them to the luminescent biomass fragrance carbon dot fluorescent probe solution respectively, mix and react for 1 minute, add them to a four-way cuvette, and use a fluorescence spectrometer to measure the fluorescence intensity of the reaction mixture at room temperature, with an excitation wavelength of 350 nm, detection wavelengths of 452 nm and 627 nm, an incident slit of 5 nm, and an exit slit of 5 nm. Repeat the experiment 3 times and take the average value of the results.
[0067] The results show that after the luminescent biomass fragrance carbon dots prepared in Example 1 were added with gold nanoclusters, the fluorescence intensity decreased due to energy resonance transfer through self-assembly. After the addition of malachite green, malachite green was bound to the surface of the gold nanoclusters, the fluorescence of the luminescent biomass fragrance carbon dots fluorescent probe was quenched, and the fluorescence signal intensity of the reaction system decreased. The fluorescence intensity at 452nm decreased slowly, and the fluorescence intensity at 627nm decreased significantly. As the concentration of malachite green increased, the fluorescence intensity of the reaction system decreased accordingly. The measurement results are as follows: Figure 3 , and presents a linear relationship within a certain range, see Figure 4 The UV absorption spectrum showed that no new absorption peak appeared after the addition of malachite green, indicating that no non-fluorescent complex was formed. Under 365nm UV light, the solution fluorescence changed from magenta to light blue.
[0068] The standard curve was drawn with the fluorescence intensity of the reaction system at 452nm divided by the fluorescence intensity of the reaction system at 627nm as the ordinate and the final concentration of the malachite green standard in the reaction system as the abscissa. The results showed that the ratio of the fluorescence intensity of the reaction system at 452nm to the fluorescence intensity of the reaction system at 627nm was proportional to the concentration of malachite green, and the two had a good linear relationship. The linear equation was: y = 0.2173x + 2.9036, R 2 It is 0.9917.
[0069] The detection limit was determined to be good linear when the malachite green concentration was between 0 and 40 μM, with a detection limit of 24.5 nM (signal-to-noise ratio S / N=3). This shows that the luminescent biomass aroma-forming carbon dots prepared in Example 1 have a high sensitivity in detecting the content of malachite green.
[0070] 2. Smartphone-Assisted Visual Sensing Performance
[0071] 1. Mix the malachite green standard and the sample to be tested with the fluorescent probe, calculate the B / (G+R) value and draw a standard curve.
[0072] Take a series of malachite green standards with different volume concentrations of 100 μM, add them to the luminescent biomass incense carbon dot fluorescent probe solution prepared in Example 1 (including 15 uL of luminescent biomass incense carbon dot solution + 90 μL of gold nanocluster solution), mix and react for 1 minute, and finally add ultrapure water to make the volume to 2 mL, so that the final concentration of malachite green is 0-50 μM.
[0073] Under 365nm ultraviolet light, photos of the luminescent biomass agarwood carbon dot fluorescent probe solution with different concentrations of malachite green were taken. After adding malachite green from low to high concentrations to the luminescent biomass agarwood carbon dot fluorescent probe solution, the color of the solution gradually changed from magenta to light blue. The color signal of the solution was converted into a digital signal (RGB) using the color recognition application (Recognize Color) in the smartphone, and the red (R), green (G), and blue (B) channel signals were recorded to calculate the B / (G+R) value.
[0074] The standard curve was drawn with B / (G+R) as the ordinate and the malachite green concentration as the abscissa. The linear relationship between the B / (G+R) value obtained by the smartphone visualization sensing system and the malachite green concentration was calculated. The B / (G+R) of the smartphone visualization sensing platform and the malachite green concentration showed a good linear relationship in the range of 0 to 50 μM. The standard linear regression equation was y=0.0081x+0.5265(R 2 =0.9975), and the corresponding detection limit was 34.8 nM. The results showed that in the process of detecting malachite green, the color of the luminescent biomass aromatic carbon dot fluorescent probe changed from magenta to blue, showing good smartphone-assisted visual sensing performance.
[0075] 2. Add the malachite green standard and the sample to be tested onto the test paper soaked with the fluorescent probe, and draw a standard curve using the calculated B / R value.
[0076] Take malachite green solutions of different concentrations in the concentration range of 0-40μM, add them dropwise to the fluorescent test paper (paper-based sensor) soaked in the luminescent biomass fragrance carbon dot fluorescent probe solution, and dry naturally. Under 365nm ultraviolet light, when the concentration of malachite green changes within 0-40μM, the color of the test paper changes from pink to blue. Use a smartphone color recognition application (color recognition) to convert the color signal of the test paper into a digital signal. Draw a standard curve with malachite green concentration as the horizontal axis and B / R as the vertical axis.
[0077] The B / R value of the paper-based sensor showed a good linear relationship with the concentration of malachite green in the range of 0-40 μM, and the standard linear regression equation was y = 0.0263x + 1.2975 (R 2 =0.9960), and the detection limit LOD was 51.4 nM. The results show that the smartphone visualized paper-based sensor based on the luminescent biomass aromatic carbon dot fluorescent probe can achieve fast and convenient visualized detection, and has good application value in the on-site visualized detection of malachite green.
[0078] 3. Determination of malachite green content in actual samples
[0079] Actual sample: The actual sample was taken from river water and filtered through a 0.22 μm membrane to evaluate its performance for actual sample analysis. Malachite green was not found in the original water sample, and the sample group constructed by the spike method: 5, 10, and 20 μM was detected by this method.
[0080] 1. The luminescent biomass aroma-forming carbon dots prepared in Example 1 were dissolved in a BR buffer solution at pH 7 to obtain a solution I; in the solution I, the volume of the luminescent biomass aroma-forming carbon dots prepared in Example 1 was 15 μL.
[0081] 2. The gold nanoclusters prepared in Example 1 were added to the pre-prepared solution I, and the volume of the gold nanocluster solution added was 90 μL. Actual samples of different concentrations constructed by the spiked method were added to the luminescent biomass aromatic carbon dot fluorescent probe solution, mixed and reacted for 1 minute, added to a four-way cuvette, and the fluorescence intensity of the reaction mixture was measured at room temperature using a fluorescence spectrometer, with an excitation wavelength of 350 nm, detection wavelengths of 452 nm and 627 nm, an incident slit of 5 nm, and an exit slit of 5 nm. The experiment was repeated 3 times, and the results were averaged.
[0082] 3. Substitute the change in the ratio of the fluorescence intensity at 452 nm to 627 nm of the reaction system into the standard curve equation y = 0.2173x + 2.9036 (R 2 is 0.9917), and the content of malachite green in the actual sample to be tested is obtained by calculation; the results show that malachite green was not detected in the river water sample, and the results of the spike recovery experiment are shown in Table 1; the recovery rate of the detection method for the above samples is between 97.7-109.0%, and the RSD (relative standard deviation) is in the range of 2.7-3.8%, indicating that this method has good reliability and accuracy, and can be used for the detection of malachite green in actual samples. The results are shown in Table 1.
[0083] Table 1 Test results of river water samples
[0084]
[0085] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes in form and details may be made without departing from the spirit and scope of the present invention.
Claims
1. A method for detecting the concentration of malachite green based on a fluorescent probe of luminescent biomass aromatic carbon dots, characterized in that: The fluorescent probe includes a luminescent biomass gypsum carbon dot solution prepared from gypsum leaves.
2. The method according to claim 1, characterized in that: The fluorescent probe also includes a bovine serum albumin functionalized gold nanocluster solution. When used, the luminescent biomass aromatic carbon dot solution and the bovine serum albumin functionalized gold nanocluster solution are mixed.
3. The method according to claim 2, characterized in that The method comprises the following steps: Step 1, respectively mixing a malachite green standard and a sample to be tested with the fluorescent probe, and setting a blank system without adding the malachite green standard or the sample to be tested, testing the mixed solution and the blank system under the same conditions, respectively measuring the dual emission fluorescence intensities, and calculating the dual emission fluorescence intensity ratio of the obtained mixed solution; The dual emission fluorescence intensity test conditions are: the fluorescence intensity is measured under the conditions of an excitation wavelength of 350nm, detection wavelengths of 452nm and 627nm, an entrance slit of 5nm, and an exit slit of 5nm; Step 2, drawing a standard curve according to the dual emission fluorescence intensity ratio of the malachite green standard obtained in step 1; the dual emission fluorescence intensity ratio is: the ratio of the fluorescence intensity at a wavelength of 452nm to the fluorescence intensity at a wavelength of 627nm; Step 3: Substitute the dual-emission fluorescence intensity ratio of the sample to be tested into the standard curve to obtain the content of malachite green in the sample to be tested.
4. The method according to any one of claim 2, characterized in that: The steps include: Step 1, mixing the malachite green standard and the sample to be tested with the fluorescent probe respectively; Step 2, converting the color signal of the mixed solution of the malachite green standard and the fluorescent probe into a digital signal RGB, recording the R, G, and B channel signals, calculating the B / (G+R) value and drawing a standard curve; Step 3: Substitute the B / (G+R) value of the sample to be tested into the standard curve to obtain the content of malachite green in the sample to be tested.
5. The method according to claim 2, characterized in that: The steps include: Step 1, respectively drop the malachite green standard solution and the sample to be tested onto the test paper soaked with the luminescent biomass fragrance carbon dot fluorescent probe, record the color change of the test paper, convert it into a digital signal RGB, and record the R and B channel signals; Step 2, drawing a standard curve according to the B / R value of the malachite green standard solution; Step 3: Substitute the B / R value of the sample to be tested into the standard curve to obtain the content of malachite green in the sample to be tested.
6. The method according to claim 2, characterized in that The steps for preparing the luminescent biomass aromatic carbon dot solution are as follows: The leaves of the jasmine tree are cleaned, dried, and made into powder; the jasmine leaf powder is fully mixed with BR buffer solution, placed in a high-pressure reactor, heated for a period of time, naturally cooled to room temperature, filtered through a filter membrane, and the clear liquid is collected, dialyzed with deionized water to obtain a luminescent biomass jasmine carbon dot solution; The mass volume ratio of the spatholobi leaf powder to the BR buffer solution is (0.10-0.30) g:10 mL, the pH value of the BR buffer solution varies in the range of 2-10, and the heating conditions are: 120-200° C., 8-16 hours.
7. The method according to claim 2, characterized in that In the preparation step of the luminescent biomass gypsum carbon dot solution, the mass volume ratio of gypsum leaf powder to BR buffer solution is 0.19 g:10 mL, the pH value of the BR buffer solution is 5; and the heating conditions are: 180° C., 12 hours.
8. The method according to claim 2, characterized in that: The preparation steps of the bovine serum albumin functionalized gold nanocluster solution are as follows: 4 mL of 1% aqueous tetrachloroauric acid solution was added to 10 mL of 50 mg / mL bovine serum albumin solution while magnetically stirring and mixed evenly. The mixture was stirred for 3 minutes. 1 mL of 1 M NaOH solution was added to the mixed solution. After stirring in the dark for 14 hours, the solution was diluted to 50 mL to obtain a bovine serum albumin functionalized gold nanocluster solution.
9. The method according to claim 8, characterized in that In the fluorescent probe, the volume ratio of the biomass aromatic carbon dot solution to the bovine serum albumin functionalized gold nanocluster solution is 15:90.